Compact waste water treatment plant for treating chemical bathroom effluents: A case study on system efficiency, in a work performed in Bom Jesus das Selvas - MA (Research, Society and Development, 2020)
The sanitary effluent treatment process is a mechanism that depends on the analysis of technical and demographic variables to specify the treatment system most suited to the demand linked to the efficiency of removing the required organic load and the intended use of the treated effluent. Thus, the objective of the present case study is to evaluate the efficiency of a compact sanitary effluent treatment system, specified and implemented, to meet a gross demand with a contribution of 71% of the effluents generated on construction fronts by chemical toilets, taking into account as premises the implantation of equipment with aerobic treatment characteristic, with activated sludge system. The methodology used was based on a bibliographic reference survey, with the compilation of technical data of the executed engineering projects and associated standards, performing analysis of the system's treatability rates, through the results obtained by monitoring reports carried out during 2015. As a result, it was possible to observe the framework of the parameters pH, temperature, sedimentable materials, floating materials, oils and greases (minerals and vegetables) within the limits of CONAMA Resolution 430/11, in addition to certifying the average reduction rate of 75 % for BOD5, that is, higher than the value of 60% established as a reference in the aforementioned resolution, attesting the efficiency of the system for treating effluents with the expected characteristics.